2023
DOI: 10.35848/1347-4065/acbd7b
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of large unitary (K, Na)NbO3 system single crystals for rapid solid-state crystal growth method

Abstract: To expand the process window for the rapid solid-state crystal growth (RSSCG) method, through which large unitary single crystals of a (K0.5Na0.5)NbO3 (KNN) system can be synthesized in a short time, we varied the dominant fabrication parameters, the B-site excess ratio and the Bi2O3 content, over a range wider than that utilized in previous studies. Unitary single crystals were obtained at the B-site excess ratios of 0.75%–1.75%; particularly, 1.00% and 1.25% were found to be suitable for the synthesis. Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Jiang et al also found that seed-free SSCG only took place within a certain range of LiBiO 3 addition [ 40 ]. Morimoto et al found that adjusting the alkali/niobium ratio and the addition of Bi 2 O 3 could control the number of single crystals that grew in K/Na-deficient samples, with too much Bi 2 O 3 addition preventing crystal growth [ 43 , 54 ]. Donor doping also affects grain-growth behaviour in BaTiO 3 and SrTiO 3 , with abnormal grain growth taking place up to a certain amount of donor dopant addition while further addition suppresses grain growth [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Jiang et al also found that seed-free SSCG only took place within a certain range of LiBiO 3 addition [ 40 ]. Morimoto et al found that adjusting the alkali/niobium ratio and the addition of Bi 2 O 3 could control the number of single crystals that grew in K/Na-deficient samples, with too much Bi 2 O 3 addition preventing crystal growth [ 43 , 54 ]. Donor doping also affects grain-growth behaviour in BaTiO 3 and SrTiO 3 , with abnormal grain growth taking place up to a certain amount of donor dopant addition while further addition suppresses grain growth [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The processing conditions, size, output ratio (defined as the% area of the top face of the sample face which was converted into single crystals), and chemical composition of the KNN single crystals grown in the present work are compared with those grown by seed-free SSCG in the literature ( Table 7 ). The KNN single crystals grown in the present work are of comparable size to those grown by seed-free SSCG [ 33 , 39 , 40 , 41 , 42 , 43 , 46 , 54 ]. The processing temperatures and times are also similar to those in previous studies of seed-free SSCG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations